2008
DOI: 10.3342/ceo.2008.1.2.86
|View full text |Cite
|
Sign up to set email alerts
|

Establishment and Characterization of an In Vitro Model for Cholesteatoma

Abstract: ObjectivesExperimental models are of importance to study the pathogenesis of middle ear cholesteatoma, however, they were not established until now. We aimed to develop in vitro model of middle ear cholesteatoma using primary keratinocytes and fibroblasts isolated from cholesteatoma tissue. HaCaT cell line was used as a "skin equivalent" and to compare the grade of homogeneity between cholesteatoma keratinocytes and HaCaT cells.MethodsPrimary keratinocytes were isolated from cholesteatoma tissue, co-cultured w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 18 publications
0
15
1
Order By: Relevance
“…BDD in cattle is associated with hyperkeratosis, keratin filament formation and spirochetal infection [12][13][14][15][16][17][18][19][20]. Hyperkeratosis and excessive keratin production associated with chronic inflammation has been demonstrated in humans with cholesteatoma [23,24], and alterations in keratinocyte expression of HLA markers and tissue enzymes have been reported in association with Bb infection [25,26]. These observations suggest that hyperkeratosis and keratin filament production associated with spirochetal infection is a plausible explanation for the clinical and microscopic findings in MD.…”
Section: Discussionmentioning
confidence: 99%
“…BDD in cattle is associated with hyperkeratosis, keratin filament formation and spirochetal infection [12][13][14][15][16][17][18][19][20]. Hyperkeratosis and excessive keratin production associated with chronic inflammation has been demonstrated in humans with cholesteatoma [23,24], and alterations in keratinocyte expression of HLA markers and tissue enzymes have been reported in association with Bb infection [25,26]. These observations suggest that hyperkeratosis and keratin filament production associated with spirochetal infection is a plausible explanation for the clinical and microscopic findings in MD.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to neoplastic transformation, several studies have revealed an association between the progression of cholesteatoma and host immune response to inflammation, such as that observed in the process of wound healing . In particular, paracrine and autocrine interactions between matrix keratinocytes and perimatrix fibroblasts play an important role in homeostasis and tissue regeneration within cholesteatomas …”
Section: Over‐reaction Of Host Immune Response To Inflammationmentioning
confidence: 99%
“…For example, TGF‐α and TGF‐β are constitutively expressed in hyperproliferative epithelium, regulating keratinocyte proliferation and differentiation in a process similar to that of the autocrine system (Fig. ) . Additionally, infiltrating inflammatory cells also secrete cytokines to stimulate the induction of hyperproliferative cells in all layers of the cholesteatoma epidermis …”
Section: Over‐reaction Of Host Immune Response To Inflammationmentioning
confidence: 99%
“…MD lesions are histopathologically distinct, however, from both hairy leukoplakia and myofibroblastic tumors. Increased keratin expression caused by upregulation of keratinocyte growth factor/fibroblast growth factor-7 has been reported in cholesteatoma, a hyperproliferative epithelial disease 22. As a consequence of B. burgdorferi infection and an inflammatory environment, dermal fibroblasts may become activated, modulating epithelial growth and differentiation through increased keratinocyte growth factor/fibroblast growth factor-7 expression 23.…”
Section: Discussionmentioning
confidence: 99%